Utilizing Instagram Data to Identify Usage Patterns Associated With Schizophrenia Spectrum Disorders - Hänsel, Katrin; Lin, Inna Wanyin; Sobolev, Michael; Muscat, Whitney; Yum-Chan, Sabrina; De Choudhury, Munmun; Kane, John M.; Birnbaum, Michael L. (Frontiers in Psychiatry, 2021)
Background and Objectives: Prior research has successfully identified linguistic and behavioral patterns associated with schizophrenia spectrum disorders (SSD) from user generated social media activity. Few studies however, have explored the potential for image analysis to inform psychiatric care for individuals with SSD. Given the popularity of image-based platforms, such as Instagram, investigating user generated image data could further strengthen associations between social media activity and behavioral health. Methods: We collected 11,947 Instagram posts across 68 participants (mean age=23.6; 59% male) with schizophrenia spectrum disorders (SSD; n=34) and healthy volunteers (HV; n=34). We extracted image features including color composition, aspect ratio, and number of faces depicted. Additionally, we considered social connections and behavioral features. We explored differences in usage patterns between SSD and HV participants. Results: Individuals with SSD posted images with lower saturation (p=0.033) and lower colorfulness (p=0.005) compared to HVs, as well as images showing fewer faces on average (SSD=1.5, HV=2.4, p<0.001). Further, individuals with SSD demonstrated a lower ratio of followers to following compared to HV participants (p=0.025). Conclusion: Differences in uploaded images and user activity on Instagram were identified in individuals with SSD. These difference highlight potential digital biomarkers of SSD from Instagram data.